The Study of Helicobacter Pylori Bacteria Infection in Bani Waleed city -Libya - Eisay, Zahrah M.; Grimida, Salheen; Abdoarrahem , Mostafa MO; Alnaqrat, Ruqayah Ali; Zobeida, Addokali (Information Technology and Science (ITScience), 2023)
The current study included 430 infected cases with H. pylori bacteria in Bani Waleed city, Libya. Risk factors that might have an important role in an increasing the risk of infection were studied such as drinking stimulants tea and coffee, and smoking. The samples were blood and faces and were tested using rapid test to find the infection. The percentage of infected people who drank both or one of the stimulants was 74%. Most of infected cases were young people between the ages of 25 to 36 years, with an infection rate of 35%. The study also showed that eating spices increased the risk of infection to 64%, however infection rate among men was higher than women at a rate of 55%, while the infection rate among women was 45%. On the other hand, study showed that the smoking was not significant, as 56% for smokers were infected, Also, the study indicated that there is no link between H. pylori infection and chronic diseases such as diabetes and blood pressure, as the results showed that 76% of the infected people do not suffer from any chronic diseases. It was also found that the two blood groups A and O are more prevalent among those infected with H. pylori bacteria, with a percentage of 31% for both types, followed by blood group B, with 26%, then blood group AB at 12%. More studies should be carried out to establish the risk factors and set a control plan.